A medium-high temperature p-type zrnisn-based semi-haasle thermal electric material, a preparation method and application thereof

CN122687364APending Publication Date: 2026-09-04DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610839832.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

[0004]本发明的目的在于,针对现有p型ZrNiSn基半哈斯勒热电材料在不引入高成本Ir元素的情况下,热电优值极低,且晶格热导率过高,难以与高性能n型支腿匹配构建中高温热电器件问题,提出一种中高温p型ZrNiSn基半哈斯勒热电材料,该热电材料在降低晶格热导率的同时,实现了n型材料向p型材料的转换,为构建高功率热电器件奠定了基础

Benefits of technology

[0032] 1) The high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material of this invention successfully changed the conductivity type of ZrNiSn-based semi-Hassler thermoelectric material by equimolar doping of Sc and Y elements at the Zr site, which significantly reduced the lattice thermal conductivity. The ZT value reached a maximum of 0.14 at 873 K, which expanded the application range of the material and is expected to be widely used in industrial waste heat and automobile exhaust waste heat.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122687364A_ABST
    Figure CN122687364A_ABST
Patent Text Reader

Abstract

The application provides a medium-high temperature p-type ZrNiSn-based half-Hasler thermoelectric material, a preparation method and application thereof. x Y x Zr 1‑2x NiSn, wherein x is a molar ratio, and the value range of x is 0.2-0.35. The medium-high temperature p-type ZrNiSn-based half-Hasler thermoelectric material provided by the application changes the majority carriers from electrons to holes, significantly reduces the lattice thermal conductivity, and obtains the p-type ZrNiSn-based thermoelectric material, thereby laying a foundation for developing high-power thermoelectric devices with matching n-type and p-type legs. The application has good application prospect and large-scale popularization potential in the fields of distributed low-grade waste heat recovery power generation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to thermoelectric materials technology, and more particularly to a medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material, its preparation method and application. Background Technology

[0002] Thermoelectric materials, as a novel type of clean energy material, rely on the Seebeck and Peltier effects to achieve the direct conversion between heat and electrical energy, and are considered one of the important candidate materials for addressing global energy challenges. The performance of thermoelectric materials is usually expressed by the dimensionless thermoelectric figure of merit ZT (ZT = S). 2 σT / κ is used as the core evaluation index. Here, S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature. κ also includes the lattice thermal conductivity (κT / κ). l ) and electronic thermal conductivity (κ) e The higher the ZT (z-t), the higher the thermoelectric conversion efficiency. High power factor (PF = S) 2 Low σ and low κ are the foundation for realizing high-performance thermoelectric materials, while n-type and p-type legs with the same type of material are the key to fabricating ideal thermoelectric devices.

[0003] ZrNiSn-based semi-Hassler compounds are considered thermoelectric materials with potential for large-scale commercial production and application due to their excellent high-temperature chemical and thermal stability, outstanding mechanical properties, and high high-temperature ZT. ZrNiSn-based semi-Hassler alloys possess excellent electrical properties, but due to their simple crystal structure, intrinsic κ... l The ZT (Zero Temperature Tolerance) is relatively high. Currently, the ZT of n-type ZrNiSn thermoelectric materials has reached 1.5, while the ZT of the p-type counterpart is only 0.3. Furthermore, the introduction of the high-cost Ir element makes it difficult to meet practical application requirements. Without the addition of Ir, the ZT of p-type ZrNiSn thermoelectric materials has not yet broken through 0.1. Therefore, how to further improve the thermoelectric performance of p-type ZrNiSn-based semi-Hassler thermoelectric materials is an urgent problem to be solved in realizing high-power, medium- and high-temperature thermoelectric devices. Summary of the Invention

[0004] The purpose of this invention is to address the problem that existing p-type ZrNiSn-based semi-Hassler thermoelectric materials suffer from extremely low thermoelectric figure of merit and excessively high lattice thermal conductivity, making it difficult to match with high-performance n-type legs to construct medium- and high-temperature thermoelectric devices, without introducing high-cost Ir elements. This invention proposes a medium- and high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material. This material reduces lattice thermal conductivity while achieving the conversion from n-type to p-type materials, laying the foundation for constructing high-power thermoelectric devices. It has promising application prospects and large-scale promotion potential in fields such as distributed generation and low-grade waste heat recovery power generation.

[0005] It should be noted that, in this invention, unless otherwise specified, the specific meaning of "comprising" in relation to composition and description includes both open-ended meanings such as "comprising," "including," etc., and closed-ended meanings such as "composed of," "consisting of," etc., and similar meanings.

[0006] To achieve the above objectives, the technical solution adopted by this invention is: a medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material, the chemical composition of which is: Sc x Y x Zr 1-2x NiSn, where x is the molar ratio, ranging from 0.2 to 0.35.

[0007] Furthermore, the value of x ranges from 0.2 to 0.25.

[0008] Furthermore, the molar amounts of Sc and Y are equal, i.e., the molar ratio of Sc to Y is 1:1. This invention achieves an n-type to p-type semiconductor transformation of ZrNiSn by equimolar doping of Sc and Y at the Zr sites of the Zr-based alloy. Simultaneously, the lattice thermal conductivity is significantly reduced, laying the foundation for fabricating n-type and p-type legs of thermoelectric devices with matched compositions.

[0009] Furthermore, the power factor of the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material is 0.14 mW / m. -1 K -2 ~ 0.74 mW m -1 K -2 .

[0010] Furthermore, the lattice thermal conductivity of the aforementioned medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material is 1.44 W / m. -1 K -1 ~ 1.92 W m -1 K -1 .

[0011] Another objective of this invention is to disclose a method for preparing a medium-to-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material, comprising the following steps:

[0012] Step (1): Weigh out the raw materials Sc, Y, Zr, Ni and Sn according to their chemical composition;

[0013] Step (2): Place the raw materials in a magnetic levitation melting furnace and melt them in a protective atmosphere;

[0014] Step (3): Place the alloy ingot obtained from smelting into a planetary ball mill and ball mill it to obtain a slurry;

[0015] Step (4): Filter and dry the slurry to obtain powder;

[0016] Step (5): The powder is sintered using spark plasma sintering technology to obtain a medium-high temperature p-type ZrNiSn-based semi-Hasler thermoelectric material.

[0017] Furthermore, in step (1), the particle size of the Sc, Y, Zr, Ni and Sn raw materials is 0.5 to 10 mm.

[0018] Furthermore, in step (2), the Sc, Y, Zr, Ni and Sn raw materials are placed in a magnetic levitation melting furnace for melting in order of their melting points.

[0019] Furthermore, the protective atmosphere in step (2) is argon.

[0020] Furthermore, the melting pressure in step (2) is 10. 4 ~10 5 Pa; the smelting is divided into heating and holding stages. The heating rate of the heating and melting stage is 300~310K / s, and the heating time is based on the complete melting of the raw materials. The holding temperature of the holding stage is 1973~2273K, and the holding time is 30~60s.

[0021] Furthermore, the melting process in step (2) is repeated 4 to 8 times to ensure the uniformity of the structure after melting.

[0022] Further, the wet ball milling in step (3) includes: first, crushing the alloy ingot with a tablet press, and then performing wet ball milling. The ball milling medium is anhydrous ethanol, the ball-to-material ratio is 15:1~20:1, the rotation speed is 300~700 r / min, and the ball milling time is 10~16 h.

[0023] Furthermore, in step (3), the preferred ball-to-material ratio for wet ball milling is 15:1 to 18:1, the preferred rotation speed is 400 to 600 r / min, and the preferred ball milling time is 12 to 14 h.

[0024] Further, the drying in step (4) includes: naturally drying the wet powder in a glove box for 12 to 48 hours.

[0025] Furthermore, in step (3), the particle size of the wet powder is 0.5–2 μm.

[0026] Furthermore, in step (5), the discharge plasma sintering temperature is 1073–1273 K, the sintering pressure is 80–110 MPa, and the holding time is 5–20 minutes.

[0027] Furthermore, in step (5), the preferred discharge plasma sintering temperature is 1073~1123K, the preferred sintering pressure is 90~105MPa, and the preferred holding time is 10~15min.

[0028] Another objective of this invention is to disclose the application of a medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material in the field of waste heat recovery power generation.

[0029] Furthermore, the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material is particularly suitable for applications in distributed, low-grade waste heat recovery power generation.

[0030] Furthermore, the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material is particularly suitable for industrial waste heat and automotive exhaust waste heat applications.

[0031] The high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material, its preparation method, and its application in this invention have the following advantages compared with existing technologies:

[0032] 1) The high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material of this invention successfully changed the conductivity type of ZrNiSn-based semi-Hassler thermoelectric material by equimolar doping of Sc and Y elements at the Zr site, which significantly reduced the lattice thermal conductivity. The ZT value reached a maximum of 0.14 at 873 K, which expanded the application range of the material and is expected to be widely used in industrial waste heat and automobile exhaust waste heat.

[0033] 2) The high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material in this invention has a high power factor, with a maximum power factor of 0.74 mW / m. -1 K -2 It possesses extremely low lattice thermal conductivity, with a minimum lattice thermal conductivity of 1.44 W / m. -1 K -1 This has significant application value for achieving high output power density in devices.

[0034] 3) The preparation method of high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material in this invention has the advantages of short process, few steps and easy control, and has the prospect of large-scale commercial production and application.

[0035] In summary, the high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material of this invention has promising application prospects and large-scale promotion potential in fields such as distributed generation and low-grade waste heat recovery power generation. Compared with previous p-type ZrNiSn thermoelectric materials, its thermoelectric performance has been significantly improved, and the cost is lower. Further improvements in ZT are expected, providing a guarantee for the construction of medium- and high-temperature, high-power thermoelectric devices. Attached Figure Description

[0036] Figure 1 For comparative examples 1-2, ZrNiSn and Sc 0.15 Y 0.15 Zr 0.7 NiSn, Sc from Examples 1-2 0.2 Y 0.2 Zr 0.6 NiSn, Sc 0.25 Y 0.25 Zr 0.5 XRD patterns of NiSn semi-Hassler thermoelectric materials;

[0037] Figure 2 For comparative examples 1-2, ZrNiSn and Sc 0.15 Y 0.15 Zr 0.7 NiSn, Sc from Examples 1-2 0.2 Y 0.2 Zr 0.6 NiSn, Sc 0.25 Y 0.25 Zr 0.5 Electrical conductivity of NiSn semi-Hassler thermoelectric materials;

[0038] Figure 3 For comparative examples 1-2, ZrNiSn and Sc 0.15 Y 0.15 Zr 0.7 NiSn, Sc from Examples 1-2 0.2 Y 0.2 Zr 0.6 NiSn, Sc 0.25 Y 0.25 Zr 0.5 The Seebeck coefficient of NiSn semi-Hasler thermoelectric materials;

[0039] Figure 4 For comparative examples 1-2, ZrNiSn and Sc 0.15 Y 0.15 Zr 0.7 NiSn, Sc from Examples 1-2 0.2 Y 0.2 Zr 0.6 NiSn, Sc 0.25 Y 0.25 Zr 0.5 Total thermal conductivity of NiSn semi-Hassler thermoelectric materials;

[0040] Figure 5 For comparative examples 1-2, ZrNiSn and Sc 0.15 Y 0.15 Zr 0.7 NiSn, Sc from Examples 1-2 0.2 Y 0.2Zr 0.6 NiSn, Sc 0.25 Y 0.25 Zr 0.5 Lattice thermal conductivity of NiSn semi-Hassler thermoelectric materials;

[0041] Figure 6 For comparative examples 1-2, ZrNiSn and Sc 0.15 Y 0.15 Zr 0.7 NiSn, Sc from Examples 1-2 0.2 Y 0.2 Zr 0.6 NiSn, Sc 0.25 Y 0.25 Zr 0.5 The thermoelectric figure of merit of NiSn semi-Hasler thermoelectric materials. Detailed Implementation

[0042] The present invention will be further described below with reference to embodiments. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0043] Unless otherwise stated, all units used in this specification are international standard units, and all numerical values ​​and ranges appearing in this invention should be understood to include systematic errors that are unavoidable in industrial production.

[0044] In this specification, the range of values ​​referred to as "value A to value B" refers to the range including the endpoint values ​​A and B.

[0045] In this specification, the numerical range indicated by "above" or "below" refers to the numerical range that includes the stated number.

[0046] In this specification, the word "may" has two meanings: to perform a certain process and not to perform a certain process.

[0047] In this specification, the terms "optional" or "optional" are used to indicate the use or omission of certain substances, components, procedures, application conditions, etc.

[0048] In this instruction manual, when "room temperature" or "room temperature" is used, the temperature can be 15-25℃.

[0049] Unless otherwise specified, all reagents or instruments used in this instruction manual are commercially available products.

[0050] This invention provides a medium-to-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material and its preparation method. The chemical composition of the thermoelectric material is: Scx Y x Zr 1-2x NiSn, where x is the molar ratio, ranging from 0.2 to 0.35.

[0051] In this invention, the value of x in the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material is preferably in the range of 0.2 to 0.25, specifically 0.2 and 0.25.

[0052] This invention also provides a method for preparing the high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material described above, comprising the following steps:

[0053] (1) According to the chemical composition of the medium-high temperature p-type ZrNiSn-based semi-Hasler thermoelectric material, the raw materials are smelted in a protective atmosphere to obtain alloy ingots;

[0054] (2) The alloy ingot is subjected to wet ball milling, drying and discharge plasma sintering in sequence to obtain the medium-high temperature p-type ZrNiSn-based semi-Hasler thermoelectric material.

[0055] According to the chemical composition of the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material, the raw materials are smelted in a protective argon atmosphere to obtain an alloy ingot. In this invention, the raw materials preferably include Sc particles, Y particles, Zr particles, Ni particles, and Sn particles; the source of the Sc particles, Y particles, Zr particles, Ni particles, and Sn particles is not particularly limited, and commercially available products well known to those skilled in the art can be used.

[0056] In a specific embodiment of the present invention, the Sc particles are preferably metallic Sc ​​with a purity of 99.99%; the Y particles are preferably metallic Y with a purity of 99.95%; the Zr particles are preferably metallic Zr with a purity of 99.95%; the Ni particles are preferably metallic Ni with a purity of 99.995%; and the Sn particles are preferably metallic Sn with a purity of 99.99%.

[0057] In this invention, the smelting preferably includes magnetic levitation smelting; the smelting preferably includes a heating stage and a holding stage; the heating rate of the heating stage is preferably 300-310 K / s, specifically 300 K / s, 302 K / s, 304 K / s, 306 K / s, 308 K / s or 310 K / s, and the time is based on the complete melting of the raw materials; the temperature of the holding stage is preferably 1973-2273 K, specifically 1973 K, 2023 K, 2073 K, 2123 K, 2173 K, 2223 K or 2273 K, and the holding time is preferably 30-60 s, specifically 30 s, 40 s, 50 s or 60 s.

[0058] In this invention, the number of melting operations is preferably 4 or more, specifically 4, 5, 6, 7 or 8 times; the melting equipment is preferably a magnetic levitation melting furnace.

[0059] In this invention, the ball milling is preferably wet ball milling; the medium for wet ball milling is preferably anhydrous ethanol; and the grinding balls used in the ball milling are preferably tungsten carbide balls.

[0060] In this invention, the sintering is preferably spark plasma sintering; the sintering temperature is preferably 1073~1273K, specifically 1073K, 1123K, 1173K, 1223K or 1273K; the pressure is preferably 80~110MPa, specifically 80MPa, 85MPa, 90MPa, 95MPa, 100MPa, 105MPa or 110MPa; the holding time is preferably 5~20min, specifically 5min, 10min, 15min or 20min; the sintering is preferably carried out in a graphite mold. This invention, through spark plasma sintering, can make the alloy interior more compact and reduce internal porosity.

[0061] To further illustrate the present invention, the following detailed description of the invention's solutions, in conjunction with the accompanying drawings and embodiments, is provided, but should not be construed as limiting the scope of protection of the present invention.

[0062] Example 1

[0063] This embodiment discloses a medium-to-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material, whose chemical composition is Sc 0.2 Y 0.2 Zr 0.6 The molar ratio of NiSn, Sc, and Y is 1:1, and the preparation method is as follows:

[0064] Raw material selection: Sc, Y, Zr, Ni, and Sn are small particles with a diameter of 0.5–10 mm. The purity of all materials is ≥99.95%.

[0065] Ingredients: According to Sc 0.2 Y 0.2 Zr 0.6 The ingredients are prepared according to the stoichiometric ratio of NiSn;

[0066] Melting: The metals are placed in a magnetic levitation melting furnace in order of their melting points, under a protective argon atmosphere and at a pressure of 10. 5 Pa. After heating to 2173K, hold at that temperature for 30s, and repeat the melting process 4 times to ensure uniform microstructure;

[0067] Ball milling: First, the ingot is crushed using a tablet press, and then wet ball milling is performed. The ball milling medium is anhydrous ethanol, the ball-to-material ratio is 15:1, the rotation speed is 500 r / min, and the ball milling time is 12 h. After wet ball milling, the powder is obtained by filtration and drying.

[0068] Drying treatment: The filtered powder is naturally dried in a glove box for 48 hours.

[0069] Sintering: The dried powder was loaded into a graphite mold and sintered using spark plasma sintering technology. The sintering temperature was 1223 K, the sintering pressure was 100 MPa, and the holding time was 15 min to obtain Sc. 0.2 Y 0.2 Zr 0.6 NiSn thermoelectric materials.

[0070] Example 2

[0071] This embodiment discloses a medium-to-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material, whose chemical composition is Sc 0.25 Y 0.25 Zr 0.5 NiSn; its preparation method is the same as in Example 1.

[0072] Comparative Example 1

[0073] This comparative example discloses a medium-to-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material with the chemical composition Sc. 0.15 Y 0.15 Zr 0.7 NiSn; its preparation method is the same as in Example 1.

[0074] Comparative Example 2

[0075] This comparative example discloses a thermoelectric material with the chemical composition ZrNiSn; the preparation method is the same as in Example 1.

[0076] The thermoelectric materials of Examples 1-2 and Comparative Examples 1-2 were tested respectively, and the test results are as follows:

[0077] XRD tests were performed on the semi-Hassler thermoelectric materials obtained in Examples 1-2 and Comparative Examples 1-2 using an X-ray diffractometer. The test results are as follows: Figure 1 As shown, from Figure 1 As can be seen, the diffraction peaks of all samples are consistent with the standard PDF card of ZrNiSn, and no characteristic impurity peaks were detected, indicating that all samples are single phases with good symmetry.

[0078] The electrical properties of the semi-Hassler thermoelectric materials obtained in Examples 1-2 and Comparative Examples 1-2 were tested using the LSR-3 electrical performance testing system. The conductivity test curves are shown below. Figure 2 As shown, the test curve for the Seebeck coefficient is as follows: Figure 3 As shown. From Figure 2 As can be seen from the data, within the entire test temperature range, Examples 1-2 Sc x Y x Zr 1-2x The conductivity of NiSn (x=0.2, 0.25) is significantly higher than that of comparative examples 1-2, ZrNiSn and Sc. 0.15 Y 0.15 Zr 0.7 Electrical conductivity of NiSn. Comparative Examples 1-2: ZrNiSn and Sc 0.15 Y 0.15 Zr 0.7 The electrical conductivity of NiSn increases with increasing temperature. As temperature increases, the conductivity of NiSn in Examples 1-2... x Y x Zr 1- 2x The conductivity of NiSn (x=0.2, 0.25) first decreases and then increases. Example 2 Sc 0.25 Y 0.25 Zr 0.5 NiSn exhibits a maximum conductivity of 17.62 × 10⁻⁶ at 923 K. 4 S m -1 .from Figure 3 As can be seen from the data, within the entire test temperature range, Examples 1 to 2Sc x Y x Zr 1-2x The Seebeck coefficient of NiSn (x=0.2, 0.25) changed from negative to positive, proving the successful transition from n-type to p-type material. Meanwhile, as the temperature increased, the Seebeck coefficient of ZrNiSn in Comparative Example 1 gradually decreased, while that of Sc in Examples 1-2 increased. x Y x Zr 1-2x The Seebeck coefficient of NiSn (x=0.2, 0.25) first increases and then decreases. Considering the combined effects of conductivity and Seebeck coefficient, Example 2 Sc 0.25 Y 0.25 Zr 0.5 NiSn achieves a maximum power factor of 0.74 mW / m at 823 K. -1 K -2 .

[0079] Figure 4 and Figure 5 The values ​​are the total thermal conductivity and lattice thermal conductivity of Examples 1-2 and Comparative Examples 1-2, respectively. From... Figure 4 and Figure 5 It can be seen that in Examples 1-2 Sc x Yx Zr 1-2x The total thermal conductivity and lattice thermal conductivity of NiSn (x=0.2, 0.25) are significantly lower than those of comparative examples 1-2, ZrNiSn and Sc. 0.15 Y 0.15 Zr 0.7 NiSn indicates that proportional doping of Zr sites with Sc and Y can effectively reduce lattice thermal conductivity. The presence of Sc and Y nanoprecipitates and dislocations can effectively scatter low- and mid-frequency phonons. Simultaneously, the decrease in phonon group velocity and increase in scattering rate also effectively reduce lattice thermal conductivity. Example 2 Sc 0.25 Y 0.25 Zr 0.5 NiSn exhibits an extremely low lattice thermal conductivity of 1.44 W / m at 923 K. -1 K -1 .

[0080] Figure 6 The thermoelectric figure of merit of Examples 1-2 and Comparative Examples 1-2 varies with temperature. Figure 6 As shown, Examples 1-2 p-type Sc x Y x Zr 1-2x The thermoelectric figure of merit of NiSn (x=0.15, 0.2, 0.25) materials increases with increasing doping concentration, but initially increases and then decreases with increasing test temperature. Thanks to the successful conversion of conductivity type and the significant reduction in lattice thermal conductivity, Example 2 Sc 0.25 Y 0.25 Zr 0.5 NiSn achieves a maximum thermoelectric figure of 0.14 at 873 K.

[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A medium-to-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material, characterized in that, Its chemical composition is: Sc x Y x Zr 1- 2x NiSn, where x is the molar ratio, ranging from 0.2 to 0.

35.

2. The high-temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to claim 1, characterized in that, The molar amounts of Sc and Y are the same.

3. The medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to claim 1, characterized in that, Its power factor is 0.14 mW / m -1 K -2 ~ 0.74 mW m -1 K -2 ; And / or, its lattice thermal conductivity is 1.44 W / m. -1 K -1 ~ 1.92 W m -1 K -1 .

4. A method for preparing a medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to any one of claims 1-3, characterized in that, Includes the following steps: Step (1): Weigh out the raw materials Sc, Y, Zr, Ni and Sn according to their chemical composition; Step (2): Place the raw materials in a magnetic levitation melting furnace and melt them in a protective atmosphere; Step (3): Place the alloy ingot obtained from smelting into a planetary ball mill and ball mill it to obtain a slurry; Step (4): Filter and dry the slurry to obtain powder; Step (5): The powder is sintered using spark plasma sintering technology to obtain a medium-high temperature p-type ZrNiSn-based semi-Hasler thermoelectric material.

5. The method for preparing the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to claim 4, characterized in that, In step (1), the particle size of the Sc, Y, Zr, Ni and Sn raw materials is 0.5 to 10 mm.

6. The method for preparing the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to claim 4, characterized in that, In step (2), the raw materials Sc, Y, Zr, Ni and Sn are placed in a magnetic levitation melting furnace for melting in order of their melting points. And / or, the protective atmosphere is argon; And / or, the melting pressure is 10. 4 ~10 5 Pa; The smelting process is divided into heating and holding stages. The heating rate of the heating and melting stage is 300~310K / s, and the heating time is based on the complete melting of the raw materials. The holding temperature of the holding stage is 1973~2273K, and the holding time is 30~60s. And / or, the number of smelting cycles is 4 to 8.

7. The method for preparing the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to claim 4, characterized in that, The wet ball milling in step (3) includes: first, crushing the alloy ingot with a tablet press, and then performing wet ball milling. The ball milling medium is anhydrous ethanol, the ball-to-material ratio is 15:1 to 20:1, the rotation speed is 300 to 700 r / min, and the ball milling time is 10 to 16 h.

8. The method for preparing the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to claim 4, characterized in that, The drying process in step (4) includes: naturally drying the wet powder in a glove box for 12-48 hours; And / or, the particle size of the wet powder in step (3) is 0.5 to 2 μm.

9. The method for preparing the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to claim 4, characterized in that, In step (5), the discharge plasma sintering temperature is 1073–1273 K, the sintering pressure is 80–110 MPa, and the holding time is 5–20 minutes.

10. The application of the medium-high temperature p-type ZrNiSn-based semi-Hassler thermoelectric material according to any one of claims 1-3 in the field of waste heat recovery power generation.